Chapter Substitutes in John Archiatros's Therapeutics - Zipser, Barbara (Istanbul Research Institute, 2018)
Ioannes Achiatros' Therapeutics are a Byzantine medical manual that has been transmitted in several versions. Of particular is here a version dating to around the late 13th century, which is written in vernacular Greek. It contains a commentary and it is clearly rooted in practical medicine outside wealthy settings. The present article examines substitutes for pharmacological ingredients that are mentioned in the commentary. For instance, the commentator could refer to drug X in case drug Y is not available. These substitutes allow us to draw conclusions on the medicines available to ordinary people at the time, a topic that is not often described.